PROBLEMS OF DEVELOPMENT OF INFRASTRUCTURE OF AVIATION COMPLEX OF RUSSIA - V. Gafiatullin (Вестник университета)
The article considers issues of functioning and development of infrastructure elements of an aircraft manufacturing complex of Russia. Special attention is paid to the study of questions connected with the transport infrastructure of our country crucial. Discusses questions of the development of educational infrastructure as an element of reproduction of personnel potential of domestic enterprises. The study was analyzed the features of development of innovation infrastructure necessary for long-term development of the industry and bridge the gap with leading Western corporations. At the end of the article justifies the thesis about the need for a systematic approach to the development of all elements of the aviation infrastructure to long-term development of the complex.